If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = -3(7 + -2n) 63 = (7 * -3 + -2n * -3) 63 = (-21 + 6n) Solving 63 = -21 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 63 + -6n = -21 + 6n + -6n Combine like terms: 6n + -6n = 0 63 + -6n = -21 + 0 63 + -6n = -21 Add '-63' to each side of the equation. 63 + -63 + -6n = -21 + -63 Combine like terms: 63 + -63 = 0 0 + -6n = -21 + -63 -6n = -21 + -63 Combine like terms: -21 + -63 = -84 -6n = -84 Divide each side by '-6'. n = 14 Simplifying n = 14
| -2x^2+y=1 | | 8c+3=10-4c | | (2/5)x-(2/7)+(9/7)x+(1/5)=1 | | 4x=-88 | | -9x+2x+3=-3x | | x^2-2x+1=x+1 | | 8b-4=-6+7b | | 6y=4x+9 | | 3-2y=7-y | | 10x+17=117 | | 3(2x+2)-4=(5x+1) | | 19+x+3-14=2 | | 0.25x+0.24=1.165 | | 10x+7=13x-5 | | 10x+7=13x+5 | | 64y^2+81=144y | | 4+3(1-2x)=37 | | -9x-8x=3+7x | | 4=14-x | | 0.07x+0.38=-0.16-0.05 | | 1.2*c+2.6*c=4.56 | | 6x=7x-2 | | -13=7+6x | | 138.88=2.85h+73.33 | | n^2+n-92=0 | | 12x-5y+30=0 | | 5a-4=2a+56 | | -5(-4u+4)-6u=2(u-7)-4 | | 23x=374737 | | 6x^2+12x=963 | | c*2.1+c*4+4=12 | | 4(3n-7)=-3(-2n+8) |